A20 Restricts Inflammatory Response and Desensitizes Gingival Keratinocytes to Apoptosis - Li, Yajie; Mooney, Erin C.; Xia, Xia-Juan; Gupta, Nitika; Sahingur, Sinem Esra (Frontiers in Immunology, 2020)
The pathophysiology of periodontal disease involves a perturbed immune system to a dysbiotic microflora leading to unrestrained inflammation, collateral tissue damage and various systemic complications. Gingival epithelial cells function as an important part of immunity to restrict microbial invasion and orchestrate the subsequent innate responses. A20 (TNFAIP3), an ubiquitin-editing enzyme, is one of the key regulators of inflammation and cell death in numerous tissues including gastrointestinal tract, skin and lungs. Emerging evidence indicates A20 as an essential molecule in the oral mucosa as well. In this study, we characterized the role of A20 in human telomerase immortalized gingival keratinocytes (TIGKs) through loss and gain of function assays in preclinical models of periodontitis. Depletion of A20 through gene editing in TIGKs significantly increased IL-6 and IL-8 secretion in response to Porphyromonas gingivalis infection while A20 over-expression dampened the cytokine production compared to A20 competent cells through modulating NF-κB signaling pathway. In the subsequent experiments which assessed apoptosis, A20 depleted TIGKs displayed increased levels of cleaved caspase 3 and DNA fragmentation following P. gingivalis infection and TNF/CHX challenge compared to A20 competent cells. Consistently, there was reduced apoptosis in the cells overexpressing A20 compared to the control cells expressing GFP further substantiating the role of A20 in regulating gingival epithelial cell fate in response to exogenous insult. Collectively, our findings reveal first systematic evidence and demonstrate that A20 acts as a regulator of inflammatory response in gingival keratinocytes through its effect on NF-κB signaling and desensitizes cells to bacteria and cytokine induced apoptosis in the oral mucosa. As altered A20 levels can have profound effect on different cellular responses, future studies will determine whether A20-targeted therapies can be exploited to restrain periodontal inflammation and maintain oral mucosa tissue homeostasis.